Argonaute and GW182 proteins: an effective alliance in gene silencing. (18th July 2013) - Pfaff, Janina; Meister, Gunter
Abstract : Argonaute proteins interact with small RNAs and facilitate small RNA-guided gene-silencing processes. Small RNAs guide Argonaute proteins to distinct target sites on mRNAs where Argonaute proteins interact with members of the GW182 protein family (also known as GW proteins). In subsequent steps, GW182 proteins mediate the downstream steps of gene silencing. The present mini-review summarizes and discusses our current knowledge of the molecular basis of Argonaute–GW182 protein interactions.